The Role of Second Chambers in the Polish and Romanian Political Systems - Dario Čepo (Anali Hrvatskog Politološkog Društva, 2007)
The paper outlines the development of bicameral legislatures, distinguishing between the British and American model of bicameralism. It also seeks to demonstrate the power of second chambers based on the diﬀerence between the unitary and federal states, presenting Arend Lijphart’s tipology of bicameral legislatures. Moreover, it tries to give a brief outline of the bicameral-unicameral dichotomy in Central and Eastern Europe, and show the questionable legitimacy of second chambers in unitary countries. Using the Senates in Poland and Romania as illustrations, it seeks to highlight their dissimilar historical-institutional development, the diﬀerences in their powers and operation and their relationship with first chambers. It also seeks to assign both Senates typologically to one of Lijphart’s four bicameral types, using six relevant variables and highlighting the main diﬀerence because of which the Polish Senate is subordinated and the Romanian Senate is equal to the first chamber.